Aquatic microbiology - Rheinheimer, G. (Wiley, 1992)
This comprehensive guide to micro-organisms in aquatic environments has been revised and updated to include recent research findings. Topics include micro-organisms and pollution, interactions between microbes and other aquatic organisms, pathogens in aquatic plants and animals, and more.